St. Paul’s discourse and dialogue with King Agrippa and Governor Festus as a model for contemporary inter-religious understanding and communication - John Samuel James Sundar, Aaron (Tattva Journal of Philosophy, 2022)
In a day in which there are different religious system vying for acceptance and probably even dominance, it is high time to identify a peaceful model for inter-religious understanding and communication. St. Paul had several interactions with the Jewish leaders, monarchs and government officials on religious topics and issues in between A.D. 60 to A.D 62 at Caesarea. His interaction with King Agrippa II and Governor Festus can be used as a paradigm for contemporary inter-religious understanding and communication. Even though Paul’s life was hanging on a balance as a prisoner about to be transported to Rome, he did not resort to violence, verbal abuse or rain down curses, when his religious claims were questioned. Instead, he argued as a seasoned philosopher, prayed as a pious saint and appealed as a prisoner in chains with humility for the ‘veracity and the reasonability’ of his truth claim. The article will interact with few philosophical themes that surface during this discourse and dialogue and also attempt to trace St Paul’s use of rhetoric in his discourse. The title of this article is ‘St. Paul’s discourse and dialogue with King Agrippa and Governor Festus as a model for contemporary inter-religious understanding and communication’. The primary source for this article is the book of Acts in the New Testament and the secondary source would be dictionaries and books.